A comparison of the Preemptive Effects of Oral Pregabalin and Gabapentin on Acute Postoperative Pain Following Lower Limb Surgery - Bhattarai, Rupak; Shah, Parasmani; Dev, Rajeev; Sarraf, Supriya; Khadka, Nisha Keshari (Birat Journal of Health Sciences, 2025)
Introduction: Postoperative pain after orthopedic surgery limits the patient’s functional status in post operative period. Therefore, optimal Postoperative pain has to be addressed to decrease perioperative morbidity and functional impairment. Both pregabalin and gabapentin has been used to treat neuropathic pain but its use in treatment of acute post operative pain following lower limb surgery has also been advocated recently. We aimed to study the preemptive effects of oral pregabalin and gabapentin on acute post operative pain following lower limb surgery. Objectives: To compare effects of oral pregabalin and gabapentin for postoperative acute pain, total analgesic consumptions, sedation and postoperative nausea and vomiting following spinal anesthesia for lower limb surgeries. Methodology: This prospective observational study was done in 90 patients divided into Group G receiving Gabapentin 600mg & Group P receiving Pregabalin 150mg one hour before surgery. The duration of postoperative analgesia, total doses of rescue analgesics, sedation score and postoperative complications at 1, 2, 6,12 and 24 hours were recorded. Results: Patients in Group P had significantly prolonged duration of postoperative analgesia as compared to Group G with 270±64.88min vs 232±42.62 minutes respectively. Rescue analgesics requirement was more in Group G 80.32±19.24 mg vs Group P 61.25 ±24.12 mg. The postoperative nausea & vomiting, Dizziness, Somnolence, Headache, Dry mouth and Mean Ramsay sedation score were comparable between two groups and were statistically insignificant. Conclusion: Though sedation being observed as a minimal perioperative side effect, the pregabalin 150 mg orally as pre-emptive increases the postoperative analgesia duration when compared with gabapentin 600mg orally following lower limp surgery under spinal anesthesia.